Characterization and overproduction of a thermo-alkaline pectate lyase from alkaliphilic Bacillus licheniformis with potential in ramie degumming. (March 2017) - Zhou, Cheng; Xue, Yanfen; Ma, Yanhe
Highlights: Pectate lyase (BliPelA) from B . licheniformis was characterized and overexpressed. Mature purified BliPelA showed maximum activity at pH 11 and 70 °C. BliPelA displayed cleavage capability on a broad range of substrates. BliPelA-treated ramie fibres reduced by 22%, indicating its degumming potential. Activity of 1450 U ml −1 and high enzyme yield of 4.5 g l −1 were achieved in E. coli . Abstract: A thermo-alkaline pectate lyase (BliPelA) gene from an alkaliphilic Bacillus licheniformis strain was cloned and overexpressed in Escherichia coli . Mature BliPelA exhibited maximum activity at pH 11 and 70 °C, and demonstrated cleavage capability on a broad range of substrates such as polygalacturonic acid, pectins, and methylated pectins. The highest specific activity, of 320 U mg −1, was towards polygalacturonic acid. Significant ramie ( Boehmeria nivea ) fiber weight loss (21.5%) was obtained following enzyme treatment and combined enzyme-chemical treatment (29.3%), indicating a high ramie degumming efficiency of BliPelA. The total activity of recombinant BliPelA reached 1450.1 U ml −1 with a productivity of 48.3 U ml −1  h −1 under high-cell-density cultivation with a glycerol exponential feeding strategy for 30 h in 1-l fed-batch fermenter, and 1380.1 U ml −1 with a productivity of 57.5 U ml −1  h −1 after 24 h under constant glucose feeding in a 20-l fermenter using E. coli as the host. The enzyme yields reached 4.5 and 4.3 g l −1 in 1-l and 20-l fed-batch fermenters, respectively, which are higher than those of most reported alkaline Pels. Based on these promising properties and high-level production, BliPelA shows great potential for application in ramie degumming in textile industry.